An Investigation into the Effects of Fibre Volume Fraction on GFRP Plate - M. R. M., Rejab; M. M., Rahman; M. M., Noor; A. N. M., Rose (2008)
This paper presents the mechanical properties of Glass Fibre Reinforce Plastic (GFRP) plates with different fibre volume fraction, Vf by considering both analytical and experimental method. The fibre used is chopped strand mat (CSM) type E-glass fibre where the matrix used is unsaturated polyester resin. The composite plates were prepared by hand lay-up technique. Rule of mixture (ROM) and modified rule of mixture (MROM) were used to predict the performance of the composite plates. Tensile test according to ASTM D 3039 was carried out to obtain ultimate strength and modulus of elasticity of the composite plate with different Vf. Three different composite systems were tested in this study. The actual Vf of the composite plates were justified by burn out test (SIRIM MS 1390:1995). MROM was found had better validity than ROM to be used to estimate the mechanical properties of specimens. The experimental results show that the mechanical properties were improved when Vf is increased. Thus, the influence of fibre volume fraction on the mechanical properties of CSM E- glass fibre/polyester composites has been evaluated.